Perancangan Arsitektur Enterprise Menggunakan Framework TOGAF ADM (Studi Kasus : UD Dirgahayu Maumere) - Maria Wihelmina Lodan; Henderikus Basilius Nong Muda; Lindiana Ermilinda (Universitas Islam Raden Rahmat, Malang, 2024)
UD Dirgahayu is a tranding business located in Maumere, Sikka Regency, East Nusa Tenggara, Indonesia which sells fertilizer and plant seeds to the public. Business processes at UD Dirgahayu still use manual systems such as sales transaction processes, making reports, checking stock, requesting product stock from suppliers, and product marketing reach is still narrow, namely only in Maumere City. This research tries to create an enterprise architecture plan to help align UD Dirgahayu’s business goals with information technology solutions to make them more effective and efficient. The method used in this research is TOGAF ADM, using five stages starting from vision architecture to opportunities and solutions. The results of this research are from a blueprint for vision architecture, business architecture, application architecture, data architecture, technology architecture, and opportunities and solutions that are expected to increase the efficiency of UD Dirgahayu’s activities.